Aquatic biota as potential biological indicators of the contamination, bioaccumulation and health risks caused by organochlorine pesticides in a large, shallow Chinese lake (Lake Chaohu). (January 2016) - Liu, Wen-Xiu; Wang, Yan; He, Wei; Qin, Ning; Kong, Xiang-Zhen; He, Qi-Shuang; Yang, Bin; Yang, Chen; Jiang, Yu-Jiao; Jorgensen, Sven Erik; Xu, Fu-Liu
Highlights: DDTs were predominant OCP components in the aquatic animals from Lake Chaohu. The mean BAF and BSSAF values for DDTs were highest among the studied OCP components. The food-web magnification factor for p, p ′-DDT was greater than 1, implying biomagnification. Culter erythropterus and Protosalanx hyalocranius would serve as bioindicators for monitoring OCP contamination. Megalobrama amblycephala would serve as a bioindicator for human carcinogenic risk of OCPs. Abstract: Aquatic biota have long been recognized as bioindicators of the contamination caused by hydrophobic organic contaminants (HOCs) in aquatic environments. The primary purpose of the present study is to identify which species of aquatic biota are the most sensitive to organochlorine pesticides (OCPs) in Lake Chaohu and can therefore serve as indicators of the lake's health and assist in the assessment of OCPs risks to human health. OCP levels in eight species of aquatic biota were measured using GC–MS, and the relationships between the biota and OCP levels in the water and suspended solids were studied. DDTs pose potential human health risks and were the predominant OCP components found in the aquatic biota. DDT had the highest mean bioaccumulation factor (BAF) and biota suspended solids accumulation factor (BSSAF) of all of the studied OCP components. The food web magnification factors (FWMF) for p, p ′-DDT were greater than 1, implying that biomagnification occurred. This finding indicates that DDTs still pose a serious threat to the ecosystem and human health in Lake Chaohu, even though the agricultural application of DDT powder has been officially banned since 1983. There were significant positive relationships between OCPs levels in Culter erythropterus and those in both water and suspended solids, as well as between OCPs levels in Protosalanx hyalocranius and those in suspended solids. This finding suggests that C. erythropterus and P. hyalocranius are the most sensitive aquatic biota to OCPs and may serve as the most effective bioindicators for monitoring OCP contamination in the water and suspended solids of Lake Chaohu. Megalobrama amblycephala, which contained the highest wet weight mean OCP concentration, is the most sensitive OCP indicator and can be used to assess the human carcinogenic risk of OCPs in Lake Chaohu.